Psoriasis induced by infliximab. - Fernandes, Iolanda C (2011)
Recently, the tumor necrosis factor-α inhibitors (anti-TNF-α) have been extensively used in clinical practice, in the treatment of several immune-mediated disorders, such as inflammatory bowel diseases, rheumatoid arthritis and more recently in psoriasis.A 35-year-old woman, suffering from Crohn's disease, diagnosed in 1994, successfully treated with infliximab at the dosage of 5 mg/Kg every 8 weeks, since 10 months ago, was referred to our Dermatology Department due to the development of erythematic-scaling confluent plaques on the scalp, back and umbilical fold. The skin biopsy confirmed the clinical diagnosis of psoriasis. Given the severity of the skin lesions and its relation with the anti-TNF-α, we decided to discontinue infliximab.Psoriasis results from the combination of polygenic predisposition and several triggering factors. Paradoxically, it has been described an increase of psoriasis induced by biologic agents. The pathogenic mechanism of such paradoxical effect has not yet been clearly elucidated.